ANTIBIOFILM SILVER NANOPARTICLES PRODUC BY ESCHERICHIA COLI - Mohammed aqeel abdulrazz; Ismaal Jmia Abas (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
coli bacteria were obtained from the soil near the Euphrates River in the northern region of Basra City and cultured on nutrient agar media. The bacterial isolate was subjected to purification and thereafter seen under a microscope. The study revealed that E. coli bacteria has the capacity to synthesize silver nanoparticles when combined with a 1 mM AgNO3 solution. The synthesis of AgNPs was deduced by examining the change in color of the reaction mixture. The UV-vis spectroscopy results indicated that the silver nanoparticles exhibited absorbance at a specific wavelength of 428 nm. Additionally, the FT-IR analysis revealed the presence of active groups in the silver particles, which played a role in maintaining their stability. The SEM and TEM studies revealed that the AgNPs exhibited a spherical morphology, with diameters ranging from 47.66 to 11.68 nm. A cubic crystal structure of silver was confirmed using an X-ray diffraction examination, while an EDX test indicated that the final product was silver (Ag). The antimicrobial efficacy of silver nanoparticles (AgNPs) against bacteria isolated from diseased patients was evaluated using the Well diffusion agar technique. It was shown that nano-silver effectively inhibited the development of the bacteria.The study utilized 96 well Microtiter plates to assess the inhibitory effect of AgNPs on biofilm development in harmful bacteria.